2011
DOI: 10.1037/a0022010
|View full text |Cite
|
Sign up to set email alerts
|

Can seeking happiness make people unhappy? Paradoxical effects of valuing happiness.

Abstract: Happiness is a key ingredient of well-being. It is thus reasonable to expect that valuing happiness will have beneficial outcomes. We argue that this may not always be the case. Instead, valuing happiness could be self-defeating because the more people value happiness, the more likely they will feel disappointed. This should apply particularly in positive situations, in which people have every reason to be happy. Two studies support this hypothesis. In Study 1, female participants who valued happiness more (vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
330
3
17

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(375 citation statements)
references
References 67 publications
25
330
3
17
Order By: Relevance
“…Recent research has suggested that valuing happiness too much may be detrimental to well-being (Mauss et al 2011). To avoid this potential problem, our manipulation directly focused on the value of the BPS activity in its own right, rather than on the value of being happy in general.…”
Section: Use Of Peer Testimonials To Manipulate Perceptions Of Activimentioning
confidence: 99%
“…Recent research has suggested that valuing happiness too much may be detrimental to well-being (Mauss et al 2011). To avoid this potential problem, our manipulation directly focused on the value of the BPS activity in its own right, rather than on the value of being happy in general.…”
Section: Use Of Peer Testimonials To Manipulate Perceptions Of Activimentioning
confidence: 99%
“…Therefore, individuals are highly motivated to find and affirm the positivity within themselves or their life circumstances. Only recently has the negative side of seeking happiness been shown to invite loneliness (Mauss, Savino, Anderson, Weisbuch, Tamir, & Laudenslager, 2012) and unhappiness (Mauss, Tamir, Anderson, & Savino, 2011) within these cultural contexts. …”
Section: Cultural Background Thinking Styles and The Idea Of Happinessmentioning
confidence: 99%
“…In line with Nozick (1989) one could ask as to whether the experience of suffering is necessary to experience a profound form of happiness. Nozick (1989) further points out that we have to be careful not to take happiness as the most important goal in life for it can prove self-defeating, this carrying the risk of disappointment should such a goal not be achieved (Mauss et al, 2011).…”
Section: Imperative Happinessmentioning
confidence: 99%